2022
DOI: 10.4103/ijo.ijo_1593_22
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a high-fidelity, virtual reality-based, manual small-incision cataract surgery simulator

Abstract: Purpose: To establish the face and content validity of the HelpMeSee Eye Surgery Simulator – a virtual reality-based cataract surgery simulator for manual small-incision cataract surgery (MSICS). Methods: The face and content validity were assessed on the sclero-corneal tunnel construction course. A questionnaire with 11 questions focused on the visual realism, with resemblance to real life surgery, and the training value of the simulator was developed. Thirty-five expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…[ 20 ] In India, Nair et al . [ 21 , 22 ] reported that novice surgeons trained on the HelpMeSee simulator for MSICS performed fewer errors in their first 20 attempts in live surgery compared with trainees who underwent standard training as per their institutional protocols without simulators. In many training programs in the United Kingdom, training on an ophthalmic surgical simulator is mandatory for third-year ophthalmology residents before live cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] In India, Nair et al . [ 21 , 22 ] reported that novice surgeons trained on the HelpMeSee simulator for MSICS performed fewer errors in their first 20 attempts in live surgery compared with trainees who underwent standard training as per their institutional protocols without simulators. In many training programs in the United Kingdom, training on an ophthalmic surgical simulator is mandatory for third-year ophthalmology residents before live cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study,[ 10 ] the authors have established the face and content validity of the HelpMeSee Eye Surgery Simulator, a virtual reality-based cataract surgery simulator for MSICS, and the authors must be congratulated for this interesting analysis. A total of 35 expert surgeons participated in the study, which is an excellent number to validate the model.…”
mentioning
confidence: 99%